EFEKTIFITAS CARA MENYIKAT GIGI TEKNIK KOMBINASI TERHADAP PLAK INDEKS (Studi Pada Murid Kelas V SDN I Sooko Mojokerto) - Silvia Prasetyowati; Endang Purwaningsih; Joko Susanto (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2018)
Introduction: Oral hygiene has significant role in oral health. Bad oral hygiene could lead to local and systemic disease. Plaque is a common causes of local dental disease. Plaque is a soft deposit, colorless, contains bacteria, and attaches to tooth surface. From a study of plaque conducted in 17th of October 2017 to 30 5th grader at SDN I Sooko Mojokerto, there were 5 students (16,67%) in good category, 10 students (33,33%) in moderate category, and 15 students (50%) in poor category. Brushing teeth is a preventive action of plaque. This action could be done in numerous technique such as horizontal, vertical, roll, Charter, Bass, Stillman-Mc Call, Fisiologis-smith, circular, and combination. Combination is the most used technique. This technique combines horizontal (back and forth), vertical (up and down), and circular. This technique could reach every part of teeth. Goal: The goal of this study is to understand the effectivity of brushing teeth using combination technique to plaque index in 5th grader at SDN I Sooko Mojokorto in 2018. Methods: The method for this study was quasi experiment with pretest and post-test. The sample was 30 students. Data collection used observation in brushing teeth and plaque index using PHP-M (Personal Hygiene Performance-Modified). Results: There was a difference in plaque index before and after brushing teeth using combination technique compared to non combination technique (p=0,000. P0,05)